Study of Central Exclusive Production of π+π−, K+K− and pairs in proton-proton collisions at GeV with the STAR detector at RHIC - STAR Collaboration (Journal of High Energy Physics, 2026)
A bstract We report on the first measurement of the Central Exclusive Production process in proton-proton collisions: pp → ph + h − p (where h = π , K , p ) at the center-of-mass energy $$\sqrt{s}=510$$ GeV with the STAR experiment at RHIC. At this energy, the process is dominated by a double Pomeron exchange mechanism. Hence, it provides a clean environment for investigating Pomeron interactions by measuring fully reconstructed final states involving only two hadrons and two forward scattered protons. The oppositely charged hadron pairs are measured within the central detector of STAR. The forward scattered protons are measured in the Roman Pot system allowing the verification of the event’s exclusivity. Differential fiducial cross sections within the STAR acceptance are presented as a function of the difference in the azimuthal angle between the outgoing protons. The invariant masses of the charged hadron pairs are measured up to approximately 3 GeV and the square of the four-momentum transfer ( t 1 and t 2 ) of the two forward-scattered protons in the range 0.3 GeV 2 < − t 1 , − t 2 < 1.6 GeV 2 . The differential fiducial cross sections of the forward protons as a function of the | t 1 + t 2 | are also presented. All results for the π + π − pair are presented in three mass ranges. A comparison with GRANIITTI Monte Carlo predictions are also presented, where the spectra include continuum and resonant contributions. The observed spectra are consistent with double Pomeron exchange, including resonances seen in previous studies.
Keywords: dept.phy

Measurement of inclusive J/ψ production in Au+Au collisions at sNN=54.4 GeV at STAR - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
This article presents measurements of inclusive J / ψ production at midrapidity (| y | < 1.0) in Au+Au collisions at sNN=54.4 GeV with the STAR detector at the Relativistic Heavy Ion Collider. A suppression of the J / ψ yield, quantified using the nuclear modification factors ( R AA, R CP), is observed with respect to the scaled production in p+p collisions. The dependence of R AA on collision centrality and J / ψ transverse momentum is measured with improved precision compared to previous measurements at 39 and 62.4 GeV, while the centrality dependence of R CP is measured and compared to the same results at 39, 62.4, and 200 GeV. In central collisions, no significant collision energy dependence of R AA is found within uncertainties for collision energies between 17.3 and 200 GeV. Two transport model calculations that include dissociation and regeneration contributions are consistent with the experimental results within uncertainties. Although no significant collision energy dependence of the J / ψ suppression in high energy heavy-ion collisions up to sNN=200 GeV is observed within uncertainties, the newly measured results at 54.4 GeV Au+Au collisions provide additional constraints on theoretical calculations of the hot medium evolution and cold nuclear matter effects. © 2026 The Authors.
Keywords: Nuclear modification factor; Quark-gluon plasma; Quarkonium; dept.phy

Evidence of Spin-Interference Effects in Exclusive 𝐽/𝜓 → 𝑒+⁢𝑒− Photoproduction in Ultraperipheral Heavy-Ion Collisions - STAR Collaboration (Physical Review Letters, 2026)
Here, we report the first evidence of spin interference in exclusive 𝐽/𝜓 → 𝑒+⁢𝑒− photoproduction in ultraperipheral heavy-ion collisions at STAR at $\sqrt{𝑠_{𝑁⁢𝑁}}$ = 200 GeV. In Au + Au collisions, a negative cos⁡(2⁢𝜙) modulation is found for 𝑝𝑇 < 120 MeV/𝑐 with a significance of 3.2⁢𝜎, while the isobar data (Ru + Ru, Zr + Zr) show a consistent negative modulation with a significance of 1.9⁢𝜎, opposite in sign to that in 𝜌0 → 𝜋+⁢𝜋− photoproduction. This establishes for the first time that the interference sign is controlled by the spin structure of the final-state daughters, resolving the ambiguity present in the all-boson 𝜌0 channel. The compact 𝐽/𝜓 probes gluon distributions at perturbative scales, resulting in a weaker modulation and providing stringent constraints on color glass condensate calculations. These findings demonstrate that spin-dependent interference in heavy vector mesons provides a new, experimentally accessible handle on gluon structure beyond traditional cross-section measurements.
Number: BNL-229705-2026-JAAM
Keywords: dept.phy

Measurement of transverse polarization of Λ and hyperons inside jets in unpolarized proton-proton collisions at GeV - STAR Collaboration (Journal of High Energy Physics, 2026)
A surprisingly large transverse polarization of Λ hyperons in unpolarized hadron-nucleon/nucleus collisions has been observed for 50 years, and the origin of this polarization remains an important open question. Recently, theoretical frameworks have advanced in describing this puzzle with the polarizing fragmentation function (PFF). We report the first measurement of Λ and transverse polarization inside jets in unpolarized proton-proton collisions, which is directly attributed to the PFF. The polarization is measured as a function of the jet transverse momentum, the fraction of the jet momentum carried by hyperons, and the transverse momentum of hyperons relative to the jet axis. Covering a wide jet-energy range, these data provide the first constraints on the gluon PFF and allow tests of TMD evolution and its universality. © The Author(s) 2026.
Keywords: Hadron-Hadron Scattering; Jets; Polarization; Proton-Proton Scattering; dept.phy

Measurement of fifth- and sixth-order fluctuations of (net-)proton number in Au + Au collisions from phase II of the beam energy scan program at RHIC - STAR Collaboration (Physical review. C, 2026)
Keywords: Beam (structure); Beam energy; Energy (signal processing); Measure (data warehouse); Phase (matter); dept.phy

Identified charged hadron production in Au + Au collisions at s N N = 54.4 GeV with the STAR detector - STAR Collaboration (Physical review. C, 2026)
We present results on the production of $π{\pm}$, $K{\pm}$, $p$, and $\bar{p}$ in Au+Au collisions at $\sqrt{s_\mathrm{NN}}$ = 54.4~GeV using the STAR detector at RHIC, at midrapidity ($|y| <$ 0.1). Invariant yields of these particles as a function of transverse momentum are shown. We determine bulk properties such as integrated particle yields ($dN/dy$), mean transverse momentum ($\langle p_{T} \rangle$), particle ratios, which provide insight into the particle production mechanisms. Additionally, the kinetic freezeout parameters ($T_\text{kin}$ and $\langle β_{T} \rangle$), which provide information about the dynamics of the system at the time of freezeout, are obtained. The Bjorken energy density ($ε_{\rm{BJ}}$), which gives an estimate of the energy density in the central rapidity region of the collision zone at the formation time $τ$, is calculated and presented as a function of multiplicity for various energies. The results are compared with those from the models such as A Multi-Phase Transport (AMPT) and Heavy Ion Jet INteraction Generator (HIJING) for further insights.
Keywords: Detector; Hadron; Large Hadron Collider; Production (economics); Star (game theory)

The solar neighborhood LIV: 54 orbits of M dwarf multiples within 30 pc with speckle interferometry at SOAR - Vrijmoet, Eliot; Tokovinin, Andrei; Henry, Todd; Winters, Jennifer; Jao, Wei‐Chun; Horch, Elliott (The Astronomical Journal, 2026)
Abstract We present 1066 speckle measurements of M dwarf multiples observed over 2021–2024, all taken with HRCam on the Southern Astrophysical Research 4.1 m telescope. Among these, 900 observations resolve companions in 212 pairs, with separations spanning 17 mas to 3 . ″ 4 and brightness differences ranging from 0 to 4.9 mag in the I filter. We have characterized the orbits of 54 of these companions, spanning periods of 0.67–30 yr, by combining our data with literature astrometry, radial velocities, and, in four cases, Hipparcos–Gaia accelerations. Among the orbits presented here are 28 that are the first-ever such characterizations for their systems and 26 that revise previously published orbits, thus providing a significant update to the observed dynamics of M dwarfs in the solar neighborhood. From these orbits, we provide new and updated dynamical total masses for these systems, precise to 0.7%–7% in nearly all cases. Future mass derivations for components in these systems will contribute to efforts in refining the mass–luminosity relation for the smallest stars and will enhance investigations of age, magnetism, and metallicity effects on luminosities at a given mass.
Keywords: Brightness; Interferometry; Metallicity; Radial velocity; Solar System; Speckle imaging; Speckle pattern; Stars; dept.phy

Measuring spin correlation between quarks during QCD confinement - STAR Collaboration (Nature, 2026)
The vacuum is now understood to have a rich and complex structure, characterized by fluctuating energy fields^1 and a condensate of virtual quark-antiquark pairs. The spontaneous breaking of the approximate chiral symmetry^2, signalled by the nonvanishing quark condensate ⟨ q q ¯ ⟩ , is dynamically generated through topologically nontrivial gauge configurations such as instantons^3. The precise mechanism linking the chiral symmetry breaking to the mass generation associated with quark confinement^4 remains a profound open question in quantum chromodynamics (QCD)-the fundamental theory of strong interaction. High-energy proton-proton collisions could liberate virtual quark-antiquark pairs from the vacuum that subsequently undergo confinement to form hadrons, whose properties could serve as probes into QCD confinement and the quark condensate. Here we report evidence of spin correlations in Λ Λ ¯ hyperon pairs inherited from spin-correlated strange quark-antiquark virtual pairs. Measurements by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC) at Brookhaven National Laboratory reveal a relative polarization signal of (18 ± 4)% that links the virtual spin-correlated quark pairs from the QCD vacuum to their final-state hadron counterparts. Crucially, this correlation vanishes when the hyperon pairs are widely separated in angle, consistent with the decoherence of the quantum system. Our findings provide a new experimental model for exploring the dynamics and interplay of quark confinement and entanglement.
Keywords: Chiral symmetry breaking; Color confinement; Hadron; Hyperon; QCD vacuum; Quantum chromodynamics; Quark; Spontaneous symmetry breaking; Symmetry breaking; Top quark; dept.phy

Probing late-stage hadronic interactions at high baryon density via K⁎0 production in the RHIC beam energy scan program - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
A precision measurement of the K ⁎0 meson yield is reported in Au+Au collisions at sNN=7.7,11.5,14.6,19.6, and 27 GeV using the high-statistics data sample collected by the STAR experiment during the Beam Energy Scan II (BES-II) program at RHIC. The transeverse momentum ( pT )-integrated yield ratios (K*0+K*0‾)/(K++K−) in central collisions show a suppression relative to peripheral collisions at the (1.7–3.6) σ level, while a thermal model without final-stage rescattering overpredicts this ratio with a deviation of (6.9–8.2) σ . These results indicate a loss of the measured K ⁎0 signal in central collisions due to re-scattering of its hadronic decay products in the hadronic phase. The pT -integrated yield of charged kaons exhibits an approximate scaling with charged-particle multiplicity, independent of collision energy and system size. A similar trend is observed for the short-lived K ⁎0 resonance, although significant deviations emerge at lower energies. At BES energies, the K ⁎0/ K ratio shows stronger suppression than at the highest RHIC and LHC energies within a given multiplicity bin, particularly in central and mid-central collisions. This behavior is consistent with changes in the effective hadronic interaction cross section and is supported by transport model calculations, which indicate dominant meson–baryon interactions at lower energies and meson–meson interactions at higher energies. Copyright © 2026. Published by Elsevier B.V.
Keywords: BES; Hadronic phase; Heavy ion collisions; Re-scattering; Resonance

Measurement of the longitudinal flow-plane decorrelation using multiplane cumulants in (Formula presented.) = 200 GeV Au + Au, Ru + Ru, and Zr + Zr collisions - STAR Collaboration (Physical Review C, 2026)
Measurements of the variation of anisotropic flow-plane angles (Ψn) with rapidity, commonly known as the flow-plane decorrelation, provide important insights into the initial conditions of the matter produced in heavyion collisions. In this paper, using data collected by the STAR experiment, we report the first measurement of the four-plane correlator observable (Formula presented.), where superscripts a, b, c, and d denote sequential pseudorapidity (η) regions with a corresponding to the most backward region, b and c close to midrapidity with nb < 0 and nc > 0, and d being the most forward. The measurement is performed for the elliptic and triangular flow (i.e., n = 2 and 3) in Au + Au and isobar (Ru + Ru, Zr + Zr) collisions at (Formula presented.) = 200 GeV. The goal of calculating the correlation of the flow-plane angle variations from backward to midcentral, and from midcentral to forward regions, is to probe the systematic variation of flow angle over a wide П range. In midcentral collisions (10-30 % centrality), we find T2{ba; dc} = —0.004 ± 0.001 (stat) ± 0.002(syst) independent of the collision system. Such a small value of T2 favors a “random-walk” variation of the flow-plane angles, where the rapidity correlation length is smaller than the entire region under study. These measurements provide new information on the decorrelation patterns in the system and offer a quantitative estimate of possible systematic variations in anisotropic flow angles such as “twist” between forward and backward regions. This opens new opportunities for understanding the three-dimensional structure and the time evolution of the quarkgluon plasma created in heavy-ion collisions. © 2026 American Physical Society
Keywords: Calibration; Cumulant; Decorrelation; Noise (video); Signal processing; dept.phy

Lignin-derived carbon dots from leaf waste as sustainable plant sunscreens and UV-protective foliar coatings - Thangavelu, Raja; Gray, Sarah; Wu, Binlin; Pellegrino, Richard; da Silva, Washington; Zuverza-Mena, Nubia; Dimkpa, Christian; White, Jason (Environmental Science Nano, 2026)
Keywords: Agricultural waste; Agriculture; Carbon fibers; Lignin; Maple; Sustainable agriculture; Sustainable production; dept.phy

Beam-energy dependence of correlations between mean transverse momentum and anisotropic flow of charged particles in Au+Au collisions at RHIC - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
The correlation between the mean transverse momentum, [p T], and the squared anisotropic flow, vn2, on an event-by-event basis has been suggested to be influenced by the initial conditions in heavy-ion collisions. We present measurements of the variances and covariance of [p T] and vn2, along with their dimensionless ratio, for Au+Au collisions at various beam energies: sNN = 14.6, 19.6, 27, 54.4, and 200 GeV. Our measurements reveal a distinct energy-dependent behavior in the variances and covariances. In addition, the dimensionless ratio displays a similar behavior across different beam energies. We compare our measurements with hydrodynamic models and similar measurements from Pb+Pb collisions at the Large Hadron Collider (LHC). These findings provide valuable insights into the beam energy dependence of the specific shear viscosity (η / s) and initial-state effects, allowing for differentiating between different initial-state models. © 2026 The Authors.
Keywords: Collectivity; Correlation; Shear viscosity; Transverse momentum correlations; dept.phy

Search for the chiral magnetic effect through beam energy dependence of charge separation using event shape selection - STAR Collaboration (Physical Review C, 2026)
High-energy, heavy-ion collisions can create local domains of chirality-imbalanced quarks, reflecting the topological features of quantum chromodynamics. The chiral magnetic effect (CME) predicts an electric charge separation of quarks in such topological domains along the magnetic field (B) generated by the passing of two high-Z nuclei. We use a correlation observable Δγ112 between charged meson pairs to detect the CME-induced charge separation and a novel event shape selection (ESS) method to mitigate the background effects related to elliptic flow (v2). The ESS method classifies events based on the emission pattern of final-state particles and determines Δγ(Formula presented) from the zero-flow limit. We reconstruct the B field direction from the spectator nucleons, which minimizes backgrounds unrelated to the collective motion of the system. In this work, we report the measurements of Δγ112 and a background indicator Δγ132 in Au + Au collisions from the Brookhaven National Laboratory Relativistic Heavy Ion Collider (RHIC) Beam Energy Scan phase II and at the top RHIC energy. After background suppression, Δγ(Formula presented) aligns with zero, and Δγ(Formula presented) is reduced to no more than 20% of Δγ112. We observe a finite residual charge separation with 2.5σ, 3σ, and 3.2σ significance in the 20-50% centrality range of Au + Au collisions at 11.5, 14.6, and 19.6 GeV. The results at 17.3 and 27 GeV also show positive values but with a lower significance of 1.3σ and 1.1σ, respectively. The corresponding ΔγΈ5ΕΕ values at 7.7, 9.2, and 200 GeV are consistent with zero within uncertainties. © (2026), (American Physical Society). All right reserved.
Keywords: Beam (structure); Charge (physics); Energy (signal processing); Event (particle physics); Magnetic field; Selection (genetic algorithm); dept.phy

Measurement of kaon directed flow in Au+Au collisions in the high baryon density region - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2026)
Rapidity-odd directed flow v 1 measurements are presented for K ± and KS0 in Au + Au collisions for sNN from 3.0 to 3.9 GeV with the STAR experiment. For comparison, v 1 of π ± , protons, and Λ from the same collisions are also discussed. The mid-rapidity v 1 slope dv1/dy|y=0 for protons and Λ is positive in these collisions. On the other hand, v 1 slope of kaons exhibits a strong pT dependence: negative at pT< 0.6 GeV/ c and positive at higher pT. A similar pT dependence is also evident for the v 1 slope of charged pions. Compared to the spectator-removed calculations in Au+Au collisions at sNN= 3.0–3.9 GeV, the JAM model demonstrates a pronounced shift of the v 1 slopes of mesons towards the negative direction. It suggests that the shadowing effect of the spectators plays an important role in the observed kaon anti-flow at low pT in the high baryon density region of non-central collisions. © 2026 The Authors.
Keywords: Directed flow; Heavy-ion collisions; High baryon density region; Kaon potential; QCD phase structure; Spectator effect; dept.phy

Observation of Charmonium Sequential Suppression in Heavy-Ion Collisions at the Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review Letters, 2026)
We report measurements of charmonium sequential suppression in Ru+Ru and Zr+Zr collisions at sNN=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The inclusive yield ratio of ψ(2S) to J/ψ as a function of transverse momentum is reported, along with the centrality dependence of the double ratio, defined as the ψ(2S) to J/ψ ratio in heavy-ion collisions relative to that in p+p collisions. In the 0-80% centrality class, the double ratio is found to be 0.41±0.10 (stat)±0.03 (syst)±0.02 (ref), lower than unity with a significance of 5.6 standard deviations. This provides experimental evidence that ψ(2S) is significantly more suppressed than J/ψ in heavy-ion collisions at RHIC. This sequential suppression pattern seems to increase from peripheral to central collisions, but with no significant dependence on the transverse momentum. © 2026 American Physical Society.
Keywords: dept.phy

Semi-inclusive direct photon + jet and π0+jet correlations measured in p + p and central Au + Au collisions at √sNN = 200 GeV - STAR Collaboration (Physical Review C, 2026)
The Solenoidal Tracker at RHIC (STAR) experiment at the Relativistic Heavy Ion Collider reports new measurements of jet quenching based on the semi-inclusive distribution of charged-particle jets recoiling from direct photon (γdir) and neutral pion (π0) triggers in pp and central Au + Au collisions at √sNN = 200 GeV for triggers in the range 9 < ET trig < 20 GeV. The datasets have integrated luminosities of 3.9 nb−1 for Au + Au and 23 pb−1 for pp collisions. Jets are reconstructed using the anti-kT algorithm with resolution parameters R = 0.2 and 0.5. The large uncorrelated jet background in central Au + Au collisions is corrected using a mixed-event approach, which enables precise charged-particle jet measurements at low transverse momentum pch T,jet and large R. Recoil-jet distributions are reported in the range pch T,jet < 25 GeV/c. Comparison of the distributions measured in pp and Au + Au collisions reveals strong medium-induced jet yield suppression for R = 0.2 with markedly less suppression for R = 0.5. Comparison is also made to theoretical models incorporating jet quenching. These data provide new insight into the mechanisms underlying jet quenching and the angular dependence of medium-induced jet-energy transport and provide new constraints on modeling such effects. © 2025 American Physical Society
Keywords: Jet (fluid); Mathematics; Physics; Thermodynamics; dept.phy

Optical Molecular Signatures of IDH Genotype for Classification of Human Glioma Using Visible Resonance Raman Spectroscopy - Zhang, Liang; Zhou, Yan; Wu, Binlin; Zhang, Shengjia; Zhu, Ke; Liu, C.; Alfano, Robert; Yu, Xinguang (Journal of Biophotonics, 2026)
Keywords: Biomarker; Gene; Genotype; Glioma; IDH mutation; IDH1; Isocitrate dehydrogenase; Mutation; Raman spectroscopy; Resonance Raman spectroscopy; dept.phy; glioma; optical molecular biopsy; visible resonance Raman spectroscopy

Measurement of medium-induced acoplanarity in central Au-Au and pp collisions at √sNN = 200 GeV using direct-photon+jet and π+ jet correlations - STAR Collaboration (Physical Review C, 2026)
The STAR Collaboration reports measurements of acoplanarity using semi-inclusive distributions of charged-particle jets recoiling from direct photon and π triggers, in central Au–Au and pp collisions at √sNN = 200 GeV. Significant medium-induced acoplanarity broadening is observed for large but not small recoil jet resolution parameter, corresponding to recoil jet yield enhancement up to a factor of ≈20 for trigger-recoil azimuthal separation far from π. This phenomenology is indicative of the response of the quark-gluon plasma to excitation, but not the scattering of jets off of its quasiparticles. The measurements are not well described by current theoretical models which incorporate jet quenching. © (2026), (American Physical Society). All rights reserved.
Keywords: Component (thermodynamics); Field (mathematics); Measure (data warehouse); Noise (video); Work (physics); dept.phy